A non-neutralizing antibody broadly protects against influenza virus infection by engaging effector cells - Ko, Yi-An; Yu, Yueh-Hsiang; Wu, Yen-Fei; Tseng, Yung-Chieh; Chen, Chia-Lin; Goh, King-Siang; Liao, Hsin-Yu; Chen, Ting-Hua; Cheng, Ting-Jen Rachel; Yang, An-Suei; Wong, Chi-Huey; Ma, Che; et al. (PLoS pathogens, 2021)
Hemagglutinin (HA) is the immunodominant protein of the influenza virus. We previously showed that mice injected with a monoglycosylated influenza A HA (HA mg ) produced cross-strain-reactive antibodies and were better protected than mice injected with a fully glycosylated HA (HA fg ) during lethal dose challenge. We employed a single B-cell screening platform to isolate the cross-protective monoclonal antibody (mAb) 651 from mice immunized with the HA mg of A/Brisbane/59/2007 (H1N1) influenza virus (Bris/07). The mAb 651 recognized the head domain of a broad spectrum of HAs from groups 1 and 2 influenza A viruses and offered prophylactic and therapeutic efficacy against A/California/07/2009 (H1N1) (Cal/09) and Bris/07 infections in mice. The antibody did not possess neutralizing activity; however, antibody-dependent cellular cytotoxicity and antibody-dependent cellular phagocytosis mediated by natural killer cells and alveolar macrophages were important in the protective efficacy of mAb 651. Together, this study highlighted the significance of effector functions for non-neutralizing antibodies to exhibit protection against influenza virus infection.